Samuel Johnson among the modernists - Lee, Anthony W. (Clemson University Press, 2019)
"Samuel Johnson Among the Modernists consists of essays penned by various hands that bring Johnson sharply into focus by framing him in an unfamiliar milieu and company, High Modernism and its aftermath. By bringing Johnson to bear on the various authors and topics gathered here, the book foregrounds some aspects of Modernism and its practitioners that would otherwise remain hidden and elusive, even as it sheds new light on Johnson"--